Development of a Mechanism of Action-Reflective Cell-Based Reporter Gene Assay for Measuring Bioactivities of Therapeutic Glucagon-like Peptide-2 Analogues - Xiaoming Zhang; Chunyan Li; Zhe Deng; Chenggang Liang; Jing Li (Molecules)
Glucagon-like peptide-2 (GLP-2) is a gut hormone that plays a pivotal role in regulating intestinal epithelial cell growth and function, making it a promising therapeutic agent for intestinal damage and bone-related diseases. Nonetheless, the therapeutic potential of GLP-2 is substantially diminished due to its inactivation by dipeptidyl peptidase 4 (DPP-4). In recent years, advancements have been made in developing dipeptidyl peptidase 4 (DPP-4) resistant GLP-2 analogues with an extended half-life. The murine model with extensive experimental bowel resection maintained on parenteral nutrition has been used for assessing the physiology and pharmacology of GLP-2, and for the preclinical validation of GLP-2 analogues. However, it possesses certain limitations, such as complex procedure, considerable variability, and time-consuming nature. Consequently, there is a pressing need for the development of a cell-based bioassay to assess GLP-2 analogues. Here, we successfully developed a mechanism-of-action (MOA)-reflective cell-based reporter gene assay (RGA), utilizing a stable HEK293 cell line expressing the GLP-2 receptor and a luciferase reporter gene. This innovative approach allows for precise quantification of the potency of GLP-2 analogues. The RGA demonstrated good accuracy, linearity, precision, and specificity, with potential applications in stability testing, drug screening, and therapeutic monitoring of GLP-2 analogues. Moreover, RNA sequencing reveals the multi-target regulatory effect of GLP-2 analogues. The establishment of this RGA provides a valuable tool for evaluating the potency of GLP-2 analogues and the screening of potential therapeutic drugs targeting to GLP-2 receptor.